Underwater acoustic characterisation of unexploded ordnance disposal using deflagration. (November 2020) - Robinson, Stephen P.; Wang, Lian; Cheong, Sei-Him; Lepper, Paul A.; Marubini, Francesca; Hartley, John P.
Abstract: The seabed off North West Europe contains much unexploded ordnance (UXO), posing a hazard to offshore developments such as windfarms. The typical removal method is through high-order detonation of a donor charge placed adjacent to the UXO. This method poses a risk of injury or death to marine mammals and other fauna from the high sound levels produced. This paper describes a controlled field experiment to compare the sound produced by high-order detonations with a low-order disposal method called deflagration, which uses a shaped charge of modest size, is less energetic, and offers reduced environmental impact from lower acoustic output. The results demonstrate a substantial reduction over high order detonation, with the peak sound pressure level and sound exposure level being more than 20 dB lower for the deflagration, and with the acoustic output depending only on the size of the shaped charge (rather than the size of the UXO). Graphical abstract: Unlabelled Image Highlights: A controlled field experiment compares acoustic output of two UXO disposal methods: deflagration and high-order detonation Substantial noise reduction for deflagration over high order (peak sound pressure level and SEL are more than 20 dB lower) Acoustic output for deflagration depends only on the size of the shaped charge (rather than the size of the UXO).